2007
DOI: 10.1002/cbic.200700401
|View full text |Cite
|
Sign up to set email alerts
|

Mutasynthesis‐Derived Myxalamids and Origin of the Isobutyryl‐CoA Starter Unit of Myxalamid B

Abstract: Myxalamids are potent inhibitors of the eukaryotic electron transport chain produced by different myxobacteria. Here, we describe the identification of the myxalamid biosynthesis gene cluster from Myxococcus xanthus. Additionally, new myxalamids (5-13) have been obtained by mutasynthesis from bkd mutants of M. xanthus and Stigmatella aurantiaca. Moreover, as these bkd mutants are still able to produce myxalamid B (2), the origin of the isobutyryl-CoA (IB-CoA) starter unit required for its biosynthesis has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 170 publications
(208 reference statements)
0
31
0
1
Order By: Relevance
“…These results were unexpected because the bkd mutants are unable to form isobutyryl-CoA starter units from valine. The authors suggested that fatty acid degradation by ␣-and ␤-oxidation of iso-odd fatty acid could be responsible for isobutyryl-CoA synthesis (37). We speculate that the ICM activity of IcmF found in both these bacteria might play a role in this process instead.…”
Section: Implications Of the Presence Of Icmfmentioning
confidence: 80%
See 1 more Smart Citation
“…These results were unexpected because the bkd mutants are unable to form isobutyryl-CoA starter units from valine. The authors suggested that fatty acid degradation by ␣-and ␤-oxidation of iso-odd fatty acid could be responsible for isobutyryl-CoA synthesis (37). We speculate that the ICM activity of IcmF found in both these bacteria might play a role in this process instead.…”
Section: Implications Of the Presence Of Icmfmentioning
confidence: 80%
“…In studies on M. xanthus and S. aurantiaca mutants in which the branched-chain ketoacid dehydrogenase was disrupted (bkd mutants), it was shown that isobutyryl-CoA is incorporated into the final product (37). These results were unexpected because the bkd mutants are unable to form isobutyryl-CoA starter units from valine.…”
Section: Implications Of the Presence Of Icmfmentioning
confidence: 99%
“…[137] Eines der wichtigsten Beispiele ist die manipulierte Biosynthese zum Avermectin-Derivat Doramectin, das klinische Anwendung als sehr wirksames Wurmmittel findet. [138] Weitere erfolgreiche Mutasynthesen lieferten neue biologisch aktive Analoga von Aureothin, [139] Rapamycin, [140,141] Borrelidin, [142] Myxalamid [143] und Ansamitocin.…”
Section: Lademechanismen Und Seltene Startereinheitenunclassified
“…To date only five compound classes derived from NRPS and PKS biosynthetic machineries have been characterized and correlated to their gene clusters in DK1622 (see Figure 1 in the Supporting Information). [8][9][10][11][12][13] Intriguingly, evaluation at the transcriptomic and proteomic levels asserts that the remaining 13 unassigned pathways are active under standard conditions for the cultivation of DK1622. [14,15] We reasoned that the low abundance of the corresponding compounds may have previously prevented their detection, and thus set out to find these compounds by utilizing advanced analytical methods.…”
mentioning
confidence: 99%